Goal-directed behavior - Aarts, Henk; Elliot, Andrew J. (New York : Psychology Press, 2012)
This volume presents chapters from internationally renowned scholars in the area of goals and social behavior. The book is organized around a series of topics that are of critical importance to understanding the social-cognitive aspects of goal-directed behavior. In each chapter, the authors offer an introduction to past research on a specific topic and combine this with a presentation of their own empirical work to provide an integrated overview of the topic at hand. As a whole, this volume is designed to provide a broad portrait of goal research as it has been and is currently being conducted in the social psychological literature. It serves as an introduction to essential issues, while at the same time offering a sampling of cutting-edge research on core topics in the study of goal-directed behavior, such as how goals are represented, where goals come from, and what goals do in the process of regulation
1. The representation and regulation of goals -- 2. The neuroscience of goal-directed behavior -- 3. Basic goal distinctions -- 4. Needs and incentives as sources of goals -- 5. Goal gradients, expectancy, and value -- 6. From goals to action -- 7. How feedback infl uences persistence, disengagement, and change in goal pursuit -- 8. Conscious and unconscious processes in goal pursuit -- 9. Goal competition, confl ict, coordination, and completion: how intergoal dynamics affect self-regulation -- 10. Control, consciousness, and agency
Includes bibliographical references and index
Keywords: Goal (Psychology); Intentionalism